A Study on the Potential of Making Quality Assessment System (Qlassic) Mandatory to the Contractors - Lee, Benny, Hai Chim; Chan, Zuo Yi; Fo, Kee Wah; Kong, Sio Kah (INTI International University, 2020)
Quality Assessment System (QLASSIC) was introduced in Malaysia in 2016 and the Construction Industry Development Board (CIDB) plans to enforce QLASSIC as mandatory for all construction projects by the year 2020. However, there has been doubts whether this is practical as the current rate of adoption is low. This research aims to study the practicality of implementing QLASSIC on all construction projects by 2020. Quantitative approach has been employed with the target respondents being G7 Contractors in Selangor .The results of this research show that, the respondents feel that QLASSIC’s mandatory status should be delayed beyond 2020,identify barriers to the implementation and provide suggestions to encourage its adoption in the industry. This research was carried out in early 2019.